The Effect of Weight Fraction on the Microstructure and Mechanical Properties of Aluminum–Cast Iron Slag Composites - Lutiyatmi, .; Surojo, Eko; Muhayat, Nurul; Azka, Muizuddin; Triyono, . (Engineering, Technology & Applied Science Research, 2025)
In the automotive industry, aluminum pistons have a limited lifespan and eventually turn into waste once they are no longer functional. Addressing the challenge of aluminum piston waste requires innovative recycling and utilization strategies. This study explores the potential of combining two waste materials, aluminum piston waste and cast-iron slag, to create Aluminum Matrix Composites (AMCs) with superior mechanical properties. To ensure uniform matrix properties, aluminum pistons from various sources were remelted into ingots before being used for composite fabrication. The AMCs were produced using the stir casting method, with cast-iron slag added as reinforcement at weight fractions of 0%, 1%, 2%, and 3%. The resulting AMCs were assessed for their microstructure, hardness, tensile strength, and corrosion resistance. The findings showed that increasing the slag content improved the particle distribution, refined the grain size, and significantly increased the hardness from 74.33 HV at 0% slag to 427.28 HV at 3% slag. The tensile strength also increased from 105 MPa with 0% slag to 245 MPa with 3% slag, although the elongation decreased from 12.5% to 5.3%. The SEM analysis revealed a transition in fracture morphology from brittle to more ductile characteristics at higher slag fractions, indicating enhanced matrix-reinforcement bonding. Furthermore, the corrosion rate declined from 0.72659 mm/year at 0% slag to 0.20 mm/year at 3% slag.